PENENTUAN KADAR KAFEIN KOPI ROBUSTA TERFERMENTASIOLEH Enterococcus durans, Enterococcus sulfureus, DAN Lactococcus garvieae - Sitaresmi Yuningtyas; Syahid Pratama Al-Wali; Winugroho (Jurnal Farmamedika (Pharmamedika Journal), 2016)
Many people like to drink coffee because it has a unique flavor. Coffee also containscaffeine,which is not good for health. One of the most famous type of coffee is civet coffee (kopi luwak).This coffee is unique because lower caffeine and in the process of this coffee should be consumedfirst by civet. The issue is populations of civet who began to decrease and the process that makes itdifficult to be produced on a large scale in a short time. In this research, we tried to apply culture ofEnterococcus durans, Enterococcus sulfureus, and Lactococcusgarviea for processing robustacoffee that resembles the civet coffee. This study aims to determine the caffeine content offermented of robusta coffee and the results will be compared with the civet coffee. Bacteria foundin the digestive system of civet had isolated and added in fermentation process of robusta coffee.Caffeine levels measured by HPLC.From these results it can be concluded that the caffeine contentin fermented of robusta coffee whichfermented using bacterial suspension Enterococcus durans,Enterococcus sulfureus andLactococcusgarvieaehad not been able to equal the caffeine content incivet coffee.Amount of caffeine in fermented of robusta coffee had lower than amount of caffeinein robusta coffee. Percentage of caffeine in fermented of robusta coffee, robusta coffee, and civetcoffeewere 1,20%, 1,90%, and 0,59% respectively.